1990
DOI: 10.1002/bms.1200191105
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization by mass spectrometry of native and recombinant human relaxin

Abstract: Mass spectrometry has played a key role in characterizing the primary structure of native and recombinant relaxin, a peptide hormone that induces ripening of the cervix prior to childbirth. The peptide is composed of two chains, A and B, and is formed from a single-chain prohormone, as is insulin. Aside from conserved cysteines, though, it has little sequence homology with insulin. Due to the small amounts of native peptide initially available (less than 10 pmol), traditional techniques could not provide infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…Several authors have found that tandem mass spectrometry, employing highenergy collision-induced dissociation, is a useful method for the characterization of disulfide-bridged peptides. Stults et al (265) applied MSlMS for the characterization of tryptic peptides during FAB analysis of recombinant human relaxin, a peptide hormone that induces ripening of the cervix prior to childbirth. The three disulfide bonds were shown to match those of insulin.…”
Section: Disulfide Bondsmentioning
confidence: 99%
“…Several authors have found that tandem mass spectrometry, employing highenergy collision-induced dissociation, is a useful method for the characterization of disulfide-bridged peptides. Stults et al (265) applied MSlMS for the characterization of tryptic peptides during FAB analysis of recombinant human relaxin, a peptide hormone that induces ripening of the cervix prior to childbirth. The three disulfide bonds were shown to match those of insulin.…”
Section: Disulfide Bondsmentioning
confidence: 99%
“…Previously, when magnetic sector instruments were widely used, high-energy CAD (HE CAD) was utilized to produce cleavage of numerous disulfide bonds in peptides. [8] The abundance of this fragmentation channel compared to lowenergy CAD has been explained by electronic excitation. Today, HE CAD can only be found in TOF/TOF instruments that are more suitable for peptides than for proteins, and for which MS n abilities are limited above n = 2.…”
mentioning
confidence: 99%
“…Alignment of the human relaxin sequence with insulin reveals that the cysteine residues involved in the intermolecular linkages are in the same position (Nguyen and Shire 1996). A process was developed at Genentech to express rDNA-derived A and B chains in E. coli and then to recombine the individually purified chains into a biologically functional molecule (Stults et al 1990). Early characterization of human relaxin by size exclusion chromatography (SEC-HPLC) suggested that the molecule exists in the monomeric form (data not shown).…”
Section: Self-association Of Small Non-glycosylated Proteinsmentioning
confidence: 99%